Could curiosity save lives? An exploration into the value of employing professional curiosity and partnership work in safeguarding adults under the Care Act 2014. Issue 5 (26th September 2019) - Thacker, Helen; Anka, Ann; Penhale, Bridget
Abstract : Purpose: The purpose of this paper is to consider the importance of professional curiosity and partnership work in safeguarding adults from serious harm, abuse and neglect. Design/methodology/approach: The paper draws on a range of materials including: review of published materials in relation to professional curiosity, reports from adult serious case reviews (SCRs) and safeguarding adult reviews (SARs); relevant materials drawn from the SAR Library, thematic reviews of SARs and Google searches; observations from practice and experience. It also refers to the relevant academic literature. Findings: Lessons from SCRs and SARs show that a lack of professional curiosity and poor coordination of support can lead to poor assessments and intervention measures that can fail to support those at risk of harm and abuse. There are a number of barriers to professionals practicing with curiosity. Working in partnership enhances the likelihood that professional curiosity will flourish. Practical implications: There are clear implications for improving practice by increasing professional curiosity amongst professionals. The authors argue that there is a scope to improve professional curiosity by utilising and developing existing partnerships, and ultimately to help reduce the number of deaths and incidents of serious harm. Originality/value: The paper considers the importance of employing professional curiosity and partnership work in safeguarding adults' practice, so enabling practitioners to better safeguard adults at risk of abuse and neglect.